Training in-service subject teachers to implement formative assessment through action research - Parmigiani, Davide; Nicchia, Elisabetta; Pario, Myrna; Murgia, Emiliana; Radović, Slaviša; Ingersoll, Marcea (Frontiers in Education, 2025)
Formative assessment is widely accepted as an essential strategy that teachers of all levels should know and use. At the secondary education level, a crucial stage in learner development, teachers are expected to actively incorporate formative assessment strategies into their subject-specific teaching and to create learning environments that consider both the teaching methods and the specific content being taught. This study reports findings from a continuing professional development (CPD) program that was designed to train in-service secondary school subject teachers to implement formative assessment strategies in their teaching practice. The main purpose of this study was to analyze the effectiveness of a CPD program about formative assessment to support teachers’ professional development. The program was developed throughout the school year 2024/25, using an action research framework to involve teachers in planning, acting, observing and reflecting on their own assessment strategies. The study involved 26 teachers who planned both self- and peer-assessment activities in their upper secondary classrooms. During and after the CPD program, teachers completed two questionnaires focused on two main issues: firstly, they had to reflect on the effectiveness of the formative assessment strategies implemented in their classrooms. Secondly, they had to consider whether the action research CPD program supported their own professional development. Findings indicate that teachers perceived formative assessment as a valuable strategy for planning activities to increase students’ cognitive, metacognitive, behavioral, and affective skills. Additionally, teachers reported that the CPD program improved both their formative assessment capacity and their skills in pedagogical content knowledge.